Conflitos ambientais em Fortaleza/Ce: as dunas do Cocó como alvo no jogo urbano - Bernardini, Camila Santiago Martins (2014)
In the context of the city, the controversies involving the use and ownership of land and natural resources were responsible for triggering some environmental conflicts. From the disorderly process of urban growth of Fortaleza, the research aims to understand how the conflict involving an area of environmental significance embedded in a zone of intense real estate appreciation occurred. Contemplated by the Municipal Act, became the Area of Relevant Ecological Interest (ARIE) Cocó Dunes in 2009. Since then is as the core of disputes being disputed environmental preservation and property rights. The methodology is qualitative and systemic. Under the interdisciplinary, three approaches build analysis: environmental, social and political-legal. For conclusive effects, it is understood that despite the historic breakthrough growth of Fortaleza, influences and political disputes, legal inconsistencies and deficit coverage in the performance of environmental movements, factors that favor the persistence of environmental conflicts persist, such as involving the Cocó Dunes.